Quantos morfotipos de labaris dos gêneros Astyanax Baird & Girard 1854, Deuterodon Eigenmann 1907 e Psalidodon Eigenmann 1911 existem na bacia do Rio Ribeira de Iguape (SP e PR, Brasil)? - Hackmann, Giovana Soares (Universidade Federal de São Carlos, 2025)
The Ribeira de Iguape River Basin has high endemism, with 104 fish species, including ‘lambaris’ from the genus Astyanax, recently split into five genera, of which only Astyanax Baird & Girard (1854), Deuterodon Eigenmann (1907), and Psalidodon Eigenmann (1911) occur in this drainage. Recent collections have revealed the existence of many morphotypes that may represent new species of these genera within the basin. Unfortunately, increasing extinction rates heighten the risk of these unknown species disappearing before they can be studied. In this context, the project aimed to identify and thoroughly describe the morphotypes of the genera Astyanax, Deuterodon, and Psalidodon (formerly Astyanax) using morphological characters. A total of 197 specimens from four collections were examined, and the initial characterization of morphotypes involved separation based on coloration patterns and body shape, followed by the measurement of 17 morphometric and 9 meristic characters. In total, 19 morphotypes were identified and characterized, some already described in the literature and others representing potential new species. The morphological variations observed in the specimens are suggested to be adaptive responses to the environmental characteristics of the region, especially the hydrological conditions. This analysis contributes to a better understanding of the existing diversity in the Ribeira de Iguape River Basin and supports future descriptions of new species. This information is crucial for implementing conservation measures in the region, as it is only possible to conserve what is known.
How many morphotypes of the tetra genera Astyanax Baird & Girard 1854, Deuterodon Eigenmann 1907 and Psalidodon Eigenmann 1911 are there in the Rio Ribeira de Iguape basin (SP and PR States, Brazil)?
Keywords: Characidae; biodiversidade; taxonomia; biodiversity; taxonomy; CIENCIAS BIOLOGICAS::ZOOLOGIA